Pembinaan narapidana di Lembaga Pemasyarakatan Klas IIA Bukittinggi dalam perspektif perencanaan - Utama, Yoko Adhytia (FIA UB, 2016)
Planning for prisoners guidance should be able to overcome the problems occurred. At the Correctional Institution Class IIA penitentiary in Bukittinggi planning do not yetÂ overcome the existing problems. This study aims to know how planning in penitentiary Klas IIA Bukittinggi. Qualitative approach is used to explore what and how planning is conducted. The findings show top down planning and a formality planning have been conducted at prisons Class IIA Bukittinggi.